Pengaruh Model Pembelajaran Kooperatif Tipe Fomulate-Share-Listen-Create (FSLC) Terhadap Kemampuan Komunikasi Matematis Siswa Kelas VIII SMP Negeri 20 Padang - WAHYUDI . (Departemen Matematika, 2019)
The capability of mathematiical communication is a base ability that each students whould have in learning, however the fact of mathematiical communiication at the grade of SMP N 20 Padang is low yet, that it needs to be improved.Learning process nowadays tend to be teacher center. To solve this problem, teacher needs to apply a learning model than canfacilitate the students in understanding the material and to build their knowledge. The learning model that can be applied is Cooperative Learning type Formulate-Share-Listen-Create (FSLC). Type of this research is a quasi-experiimental with Static Group Design. Base in data analysis that using the t test obtained P -value = 0.019 < α = 0.05, we deduce that the capability of mathematiicalncommunication in students by using Cooperative type FSLC is better than the students that learn by using conventional learning.Keywords–cooperatif learning, Formulate-Share-Listen-Create, mathematical communication, conventional learning